2016
DOI: 10.1590/1809-4430-eng.agric.v36n3p525-536/2016
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores de produção e qualidade da fibra do algodoeiro fertirrigado com água residuária sanitária

Abstract: RESUMO:Problemas decorrentes da descarga de esgoto sanitário em rios são fatores preocupantes, por reduzir a qualidade da água, principalmente na região semiárida. Como alternativa viável, a utilização agrícola de águas residuárias pode minimizar problemas ambientais e fornecer nutrientes bem como parte da exigência hídrica de plantas cultivadas. Assim, objetivou-se verificar a influência da água residuária sanitária tanto na forma bruta (ARB) quanto na tratada, em nível terciário (ART), em substituição à adub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
2
0
2
Order By: Relevance
“…The results obtained in this study were consistent with the standards required by the textile industry, and treatment with TDS, regardless of the regime adopted, proved to be sufficient to promote the development of finer fibres, presenting a MIC of 3.9 µg pol −1 , about 19% lower than MIC values observed for the control treatment. The authors of [43] reported that finer fibres resulted from the cultivation of cotton with treated wastewater; thus, corroborating the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in this study were consistent with the standards required by the textile industry, and treatment with TDS, regardless of the regime adopted, proved to be sufficient to promote the development of finer fibres, presenting a MIC of 3.9 µg pol −1 , about 19% lower than MIC values observed for the control treatment. The authors of [43] reported that finer fibres resulted from the cultivation of cotton with treated wastewater; thus, corroborating the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Although K fertilizers did not appear to be limiting to fibre quality, water deficit, or water excess with TDS affected the fibre length and short fibre index. The increment in UHM caused by the increase in water replacement up to 98.7% of the ET C (Figure 8c) indicated that the soil could be enriched with various nutrients, including K, through the use of TDS as irrigation water [18,42,43]. In our study, this raised soil fertility of more Mg +2 , K + , and NO 3 − provided by the TDS water possibly favoured cell development and, consequently, a greater fibre elongation, in agreement with what was previously discussed by others [1,35].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the health safety of using vegetation irrigated with wastewater in animal feed, there are several studies that show that the risk is low, especially if the application is interrupted for 2 weeks (Alves et al, 2017;Silva et al, 2016;Santos et al, 2016;2017). One of the studies shows that the health of animals fed with fertirrigated products was not affected and that most of the heavy metals remain in the roots (Lopes et al, 2020).…”
Section: Totalmentioning
confidence: 99%
“…Santos et al (2016), avaliando o crescimento de algodoeiro irrigado com água residuária no semiárido de Minas Gerais, também identificaram um aumento em dias para geração de uma folha em algodoeiro herbáceo, com o decorrer das fases.Outro fator importante é que a planta de algodoeiro herbáceo necessita acumular unidades de calor para que ocorra a diferenciação da gema vegetativa para reprodutiva que segundo Bakere Landivar (1991), podendo demorar de 49 a 65 DAE a depender da região até a primeira flor branca. No trabalho em questão, as primeiras flores brancas foram avistadas aos 54 DAE, sendo que em cada ramo reprodutivo simpodial o botão, flor e maçã é acompanhado por uma folha responsável pelo fornecimento de fotoassimilados, o que faz com que diminua o crescimento em número de folhas no ramo principal, mas aumenta nos laterais reprodutivos.…”
unclassified